(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Medical Laboratory Technology (MLT) is a important allied health profession responsible for performing diagnostic tests on biological specimens to support clinical diagnosis, monitor patient health, and guide treatment decisions. Accurate laboratory investigations are pivotal, particularly in life-threatening situations, necessitating the presence of well-equipped teaching laboratories affiliated with hospitals to train competent medical laboratory professionals. Objective: This study aims to evaluate the existing training standards of MLT programs across Pakistani institutions, identifying professional criteria fulfillment and highlighting prevalent shortcomings in educational and clinical training frameworks. Methods: A comprehensive desk review was conducted using data extracted from 185 Pakistani institutions offering MLT courses. The study analyzed curricula, clinical training affiliations, and certification provisions from institutional websites and official publications. Institutions were categorized into four grades (A to D) based on their compliance with core professional and educational requirements. Results: Only 18 institutions (9.72%) met the criteria for Grade A, providing comprehensive training including clinical attachments, standardized curricula, and certification support. Seventeen institutions (9.18%) achieved Grade B, while the majority, 84 institutions (45.40%) were graded C, and 66 institutions (36.67%) were Grade D, reflecting significant gaps in clinical training, curriculum standardization, and professional certification. Conclusion: The findings underscore the critical need for standardization and improvement in MLT education in Pakistan. Many institutions lack essential job training facilities within teaching hospitals and proper clinical affiliations, compromising the quality of graduate competencies. Establishing rigorous accreditation standards and enforcing curriculum uniformity are imperative to produce skilled medical laboratory professionals capable of supporting effective healthcare delivery.